MODIFIKASI ALAT PERAGA IVA TES UNTUK MELAKUKAN KETERAMPILAN DETEKSI DINI KANKER SERVIKS - Catur Anita Sari; Rico G Latumahina (LPPM Universitas Abdurrab, 2024)
Background: The competence area that must be had by midwives is clinical skills in midwifery practice on women's reproductive health and sexuality services where midwife graduates must be able to know early detection, complications, and problems of women's reproductive health and sexuality. Phantom which is commonly used in IVA examination practice in the laboratory uses phantom that cannot describe the results of the examination interpretations. The phantom used only teaches the use of speculum and cannot show Squamo-columnar junction (SCJ), so it is necessary to develop a tool that can be used to perform IVA tests that can show portio before and after acetic acid. Research Objective: modify and utilize phantoms that are no longer feasible in a new teaching tool for the IVA Test practicum and test the feasibility of the developed tools. Method: This research is a development research that produces products with the One Shot Case Study method. Results: From the 35 respondents who participated in the field trial, the total questionnaire score obtained was 6,949 with a total ideal maximum score of 7,350. The percentage of eligibility obtained is 95%. Conclusion : Modification of IVA test examination props is Very Feasible to be used as IVA test props to perform cervix cancer early detection skills in a comprehensive application-based obstetric laboratory. It is recommended for all PLP in Indonesia to be able to develop creative and innovative ideas and ideas in the laboratory in utilizing teaching aids that are no longer suitable for use into new tools that increase the use value and benefits to support learning in the laboratory